Highly sensitive up-conversion thermometric performance in Nd3+ and Yb3+ sensitized Ba4La2Ti4Nb6O30 based on near-infrared emissions. (January 2019) - Shi, Yong; Yang, Fengming; Zhao, Chuanzhen; Huang, Yan; Li, Mengzhu; Zhou, Qingjun; Li, Qiuyue; Li, Zepeng; Liu, Junming; Wei, Tong
Abstract: Up-conversion (UC) oxides comprise a huge family of materials with abundant optical functionalities and they merit extensive research. Some members of this family have been modified with proper rare earth (RE 3+ ) ions and their importance has recently been established in non-contact temperature sensors, although the thermal sensitivity (S) value was still low. In this study, we investigated Nd 3+ and Yb 3+ sensitized Ba4 La2 Ti4 Nb6 O30 (BLTN:xNd 3+ /Yb 3+ ) with a tungsten bronze structure for use as optical thermometers for the first time. Under excitation at 980 nm, obvious near-infrared emissions corresponding to 4 F7/2 / 4 S3/2  →  4 I9/2, 4 F5/2 / 2 H9/2  →  4 I9/2, and 4 F3/2  →  4 I9/2 transitions were observed, and the UC mechanism involved was elaborated. Furthermore, the UC thermometric properties were investigated according to the fluorescence intensity ratio technique and the maximum S values determined for BLTN:xNd 3+ /Yb 3+ (x = 0.12 and 0.16) samples were both higher than 0.03 K –1 . The potential of BLTN:xNd 3+ /Yb 3+ for use in optical thermometers was estimated based on comparisons with other active materials. Highlights: Tungsten bronze material used as an optical thermometry host material. Novel BLTN:xNd 3+ /Yb 3+ samples synthesized via a simple solid state reaction. Structure, up-conversion, and temperature sensing behavior investigated. Sensitivities of BLTN:xNd 3+ /Yb 3+ (x = 0.12 and 0.16) higher than 0.03 K –1 .